A novel approach using hand-held echocardiography to guide the diagnosis of heart failure in pregnant women in a low-resource setting; Maternal and Perinatal Health Research Collaboration. (25th November 2020) - Alsharqi, M; Arnold, L; Dockerill, C; Baigent, C; Leeson, P; Nair, M
Abstract: Background: Point of care imaging devices are promising tools for cardiovascular imaging in low-resource settings. Purpose: Our aim was to determine whether hand-held echocardiography scans performed by obstetricians can help to identify the cardiac phenotypes in pregnant women with heart failure in India. Methods: In November 2018, eighteen obstetricians from 10 hospitals across the states of Assam, Meghalaya and Uttar Pradesh were given 2 days of hands-on training in image acquisition using Philips Lumify devices. Obstetricians were asked to follow a simplified protocol of image acquisition and optimisation designed by the Oxford Cardiovascular Clinical Research Facility team. The protocol includes 3 key echocardiography views; parasternal long axis, parasternal short axis, and apical four chamber. Remote supervision and constructive feedback on performance was provided to improve image quality. Echocardiographic images of 269 pregnant women (with and without suspected heart failure) were acquired by the trained obstetricians, between February 2018 and January 2020. The first 147 scans were transferred with end-to-end encryption to the University of Oxford Research Echocardiography Core Laboratory (ORECL). Image interpretation and formal quality assessment was performed by 2 experienced echocardiographers. Results: Parasternal long axis image quality was assessed as good in 78.3%, and was superior to both the parasternal short axis view (76.5%) and the apical 4-chamber view (61.9%). Image depth and gain optimisation was the main reason for loss of quality. The acquisition quality was related to reported clinical disease severity, and advanced pregnancy status. Left ventricular systolic function was impaired in 32 participants (21.9%), and 23.3% of the cohort had a dilated left atrium. Rheumatic heart disease was found in 12 participants (8.3%), in which the mitral valve was stenotic; 10 severe and 1 moderate. Mitral regurgitation was reported in 29 cases (20.8%); 6 severe, 7 moderate and 16 mild. Tricuspid and aortic valve abnormalities were also detected. Pericardial effusion was reported in 45 participants (30.8%). Conclusion: Obstetricians with supervised training, using hand-held echocardiography have demonstrated acceptable image acquisition quality which could be assessed through core laboratory analysis to detect cardiac abnormalities. Such an approach could be useful to guide the diagnosis of heart failure in pregnant women in low-resource settings. Further training for the obstetricians and image quality assurance have been implemented in the ongoing MaatHRI study with plans to conduct a validation analysis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Medical Research Council (MRC), UK Fellowship for M Nair.